Gestión de riesgos ergonómicos en los puestos de trabajo de la empresa Agrobest S.A. de la comunidad Gatazo Zambrano. - Chuquimarca Lema, Luis Bolívar (2023)
This study was developed within the framework of the Engineering, Industry and Production research line, motivated by the urgency to identify and evaluate ergonomic risks in Agrobest S.A. Through a situational diagnosis and a questionnaire focused on ergonomic risk factors and their effects, the prevalence of forced postures and repetitive movements in the evaluated positions was evidenced. After surveying the 9 employees, a recurrent discomfort in the neck, back and shoulders was highlighted. For a rigorous evaluation of these risks, methods such as REBA, ROSA, OCRA and the RULER tool were applied, determining a "Very high" risk level in several work tasks. Based on these conclusions, a specific manual of postural procedures was developed for the company. This manual aims to minimize ergonomic risks, promoting a safe and beneficial work environment for all. With its application, the aim is to reduce musculoskeletal disorders, thus enriching the well-being at work in the company.